Current updates on fungal endocarditis. Issue 1 (January 2018) - Negi, Neema; Ahmad, Aijaz
Abstract: Fungal endocarditis (FE) is a rare disease but in recent years its incidence as well as mortality is increasing particularly in developing nations. Candida and Aspergillus species occupy the prominent position as etiological agents of this invasive disease. Intravenous devices such as pacemakers, central line related thrombosis and prolonged use of antibiotics are major risk factors for FE. The epidemiology of endocarditis cases is also evolving over time with exceptionally rare species causing more invasive disease. Research over the last decade has also delineated the underlying pathogenic mechanism of FE. Improved understanding of these mechanisms will help to combat the increasing problem of antimicrobial drug resistance. The diagnosis of FE is dependent on the sensitivity and specificity of the method as fungi generally do not grow well in blood cultures. More advanced techniques including molecular and immunological assays now play a central role in accurate identification of causative fungal pathogens especially in culture negative scenario. In developing nations such as India, blood culture reports are generally negative due to prior antibiotic therapy. Echocardiography has emerged as the potential imaging technique for identifying invasive endocarditis including small masses of vegetation or abscess. Successful treatment often requires both the surgical interventions and prolonged antifungal therapy. In the present review, we briefly highlight the mechanisms of pathogenesis of this rare emerging disease along with the risk factors involved, the diagnostic criteria and the treatment strategy.